2019
DOI: 10.1186/s41073-019-0067-5
|View full text |Cite
|
Sign up to set email alerts
|

Policy driven changes in animal research practices: mapping researchers’ attitudes towards animal-free innovations using the Netherlands as an example

Abstract: Background Reducing the number of animals used in experiments has become a priority for the governments of many countries. For these reductions to occur, animal-free alternatives must be made more available and, crucially, must be embraced by researchers. Methods We conducted an international online survey for academics in the field of animal science ( N = 367) to explore researchers’ attitudes towards the implementation of animal-free innovat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…For instance, setting specific objectives both in terms of time and implementation level, e.g. as done by the Dutch "2025-goal" [16], may help to better engage communication between the government, researchers and the public, and to smooth active implementation of the 3Rs. In this regard, consolidating the existing legal apparatus by reinforcing the role of organizational and institutional culture should be prioritized, as some authors suggest that they are more influential than legal demands in achieving 3R improvements [36].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, setting specific objectives both in terms of time and implementation level, e.g. as done by the Dutch "2025-goal" [16], may help to better engage communication between the government, researchers and the public, and to smooth active implementation of the 3Rs. In this regard, consolidating the existing legal apparatus by reinforcing the role of organizational and institutional culture should be prioritized, as some authors suggest that they are more influential than legal demands in achieving 3R improvements [36].…”
Section: Plos Onementioning
confidence: 99%
“…"The extensive focus on the welfare of laboratory animals will hinder scientific breakthroughs" (07; 15; 78) Van Luijk 2013[23] "Application of the 3Rs slows down innovation" (00; 20; 80) Q24: 3R implementation can have a bad impact on the career Bressers 2019[16] "Would you consider migrating due to stricter governmental legislation"(46; 23; 31) Q25: 3R implementation leads to non-comparable dataBressers 2019[16] "Reliability is a roadblock for implementation and development of alternatives" (89; 05; 06)Edwards 2015[17] "Difficulty in predicting activity in isolated tissue compared to the complex integrated in vivo situation is a barrier to the use of human tissue" (25; 00; 75)…”
mentioning
confidence: 99%
“…Additionally, the choice of animal model has been shown to depend on the historical use of animals rather than the most valid scientific approach [ 11 ]. Perhaps it is not surprising that a survey of animal researchers revealed their perception of several roadblocks hampering the development and implementation of animal-free tools [ 12 ], and this may be (partly) associated with a lack of formal education in, and exposure to, the innovative, non-animal approaches, as we discuss later. Thus, we suggest that all of these factors, and probably more, are underpinning the continued use of animals.…”
Section: The Current Situation—sustained Reliance On Animals Across T...mentioning
confidence: 99%
“…Recent research [15,16] has mapped current barriers to the implementation of animalfree methods, delivering a complex landscape of governmental, regulatory, and societal roadblocks that need to be addressed to facilitate the transition. Inadequate funding for non-animal research, lack of data sharing among research institutions, and outdated regulatory requirements are often identified as important constraints.…”
Section: Introductionmentioning
confidence: 99%